2015
DOI: 10.5194/acp-15-9159-2015
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of collection efficiency of sub-micrometer aerosol particles by cloud droplets on a single-droplet basis

Abstract: Abstract. An experimental setup has been constructed to measure the collection efficiency (CE) of sub-micrometer aerosol particles by cloud droplets. Droplets of a dilute aqueous ammonium sulfate solution with an average radius of 21.6 µm fall freely into a chamber and collide with sub-micrometer polystyrene latex (PSL) sphere particles of known sizes and concentrations. Two relative humidity (RH) conditions, 15 ± 3 % and 88 ± 3 %, hereafter termed "low" and "high", respectively, were varied with different par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 51 publications
4
32
0
Order By: Relevance
“…Moreover, the collection kernel might not incorporate all processes relevant for collections among aerosols and droplets. For instance, Brownian diffusion might increase the collection of smaller particles (e.g., Ardon-Dryer et al, 2015) but might not lead to collectional activation since it will predominantly add aerosol mass and only a small amount of water 8352 F. Hoffmann: Collectional activation (cf. Sect.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Moreover, the collection kernel might not incorporate all processes relevant for collections among aerosols and droplets. For instance, Brownian diffusion might increase the collection of smaller particles (e.g., Ardon-Dryer et al, 2015) but might not lead to collectional activation since it will predominantly add aerosol mass and only a small amount of water 8352 F. Hoffmann: Collectional activation (cf. Sect.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Oeste (2004) suggested and Wittmer et al (2015a and Figure 2 illustrates this climate cooling mechanism by the ISA method with a simplified chemical reaction scheme: a direct cooling of the troposphere by CH 4 oxidation induced by ISA particles. At droplet or particle diameters below 1 µm (between 1 and 0.1 µm), contact or coagulation actions between the particles within aerosol clouds are retarded (Ardon-Dryer et al, 2015;Rosenfeld and Freud, 2011;Santachiara et al, 2012;Wang et al, 1978). Otherwise the aerosol lifetime would be too short to bridge any intercontinental distance or arrive in polar regions.…”
Section: Oxidation Of Methane and Other Ghgsmentioning
confidence: 99%
“…Several mechanisms are usually considered, which are summarised hereafter; however, a more exhaustive review can be found in the literature (Pruppacher et al, 1998;Chate, 2005;Ladino et al, 2013;Ardon-Dryer et al, 2015). The three main mechanisms leading to this collection are Brownian motion, inertial impaction and interception.…”
Section: Theoretical Description Of Washoutmentioning
confidence: 99%
“…Classical piezoelectric drop-on-demand systems may produce electrically charged droplets (Ardon-Dryer et al, 2015). However, we want to limit electro-scavenging as Beard (1974) did in his simulations.…”
Section: Production Of Drops Representative Of Rainmentioning
confidence: 99%